Exponential synchronization of nonlinear complex networks via intermittent pinning control on time scales. (August 2020) - Wang, Boyu; Zhang, Yijun; Zhang, Baoyong
Abstract: This paper considers the synchronization problem of nonlinear complex dynamical networks (CDNs) through intermittent pinning control approach on time scales. Both the internal delay and coupling delay are considered in the nonlinear CDNs. To deal with the nonlinearity in the delayed complex network, a new scale-limited differential inequality is proposed. Based on the Lyapunov approach and the theory of time scales, some novel exponential synchronization criteria are derived, which are applicable not only to the continuous/discrete CDNs but also to the case of continuous–discrete hybrid time domains. Two numerical examples are provided to certify the validness of the proposed design method.